Medical Evidence Influence on Inpatients and Nurses Pain Ratings Agreement. (28th April 2016) - Samolsky Dekel, Boaz Gedaliahu; Gori, Alberto; Vasarri, Alessio; Sorella, Maria Cristina; Di Nino, Gianfranco; Melotti, Rita Maria
Abstract : Biased pain evaluation due to automated heuristics driven by symptom uncertainty may undermine pain treatment; medical evidence moderators are thought to play a role in such circumstances. We explored, in this cross-sectional survey, the effect of such moderators (e.g., nurse awareness of patients' pain experience and treatment) on the agreement between n = 862 inpatients' self-reported pain and n = 115 nurses' pain ratings using a numerical rating scale. We assessed the mean of absolute difference, agreement ( κ -statistics), and correlation (Spearman rank) of inpatients and nurses' pain ratings and analyzed congruence categories' (CCs: underestimation, congruence, and overestimation) proportions and dependence upon pain categories for each medical evidence moderator (χ 2 analysis). Pain ratings agreement and correlation were limited; the CCs proportions were further modulated by the studied moderators. Medical evidence promoted in nurses overestimation of low and underestimation of high inpatients' self-reported pain. Knowledge of the negative influence of automated heuristics driven by symptoms uncertainty and medical-evidence moderators on pain evaluation may render pain assessment more accurate.